Hydrodynamic coefficients of manoeuvring for small vessels - Loh, Sheau Ping (2004)
Manoeuvring analysis of a small vessel is more complex as compared to the conventional merchant ship. For small vessels such as fishing vessels, those have a relatively small prismatic coefficient as compared to large ships, would have less restoring force. On the other hand, the hydrodynamic heeling moment caused by yaw and sway at higher operational speed will become significantly high. As a consequence, the roll motion should not be neglected in the analysis of manoeuvring for small vessel, as it is in the case of big ships. The analysis for small vessels would involve at least 4-degrees of freedom and non-linearity of the forces and motions would have to be considered. During turning (yawing), the centrifugal force acting and also the developed hydrodynamic pressures surrounding the hull will induce a rolling moment. This moment will force the vessel to list either inward or outward with the turning path depending on the height of the centre of the mass. Conjunction with the development of the ship simulator in marine technology laboratory, a study on the hydrodynamic coefficient of manoeuvring has been conducted on fishing vessels. The mathematical model of manoeuvring has been reviewed in order to incorporate the heel angle effect. By conducting the experiment in the towing tank, the coefficients in the mathematic model are obtained. In this study, the effects of heel angle on the hydrodynamic coefficients have been studied. The coefficients that obtained from model testing have been used in the time domain simulation and the manoeuvring criteria of the vessel have been simulated.